EFFECT OF FISCAL DISCIPLINE ON PUBLIC EXPENDITURE ALLOCATION: EMPIRICAL EVIDENCE FROM KOGI STATE, NIGERIA - EJIGBO, A.; AGBAJI, J. S.; AGBAJI, J. S. (Kashere Journal of Management Sciences, 2025)
This study provides an empirical investigation into the relationship between fiscal discipline and the allocation of public expenditure in Kogi State, Nigeria, during the period 2007-2017. Against a backdrop of widespread fiscal mismanagement and poor human development outcomes in many Nigerian states, this research quantifies how key fiscal variables (specifically the fiscal deficit, internally generated revenue (IGR), and federal allocations) influence capital expenditures directed towards social sectors. Utilizing secondary data sourced from the Kogi State Annual Reports and the Office of the Auditor-General, an Ordinary Least Squares (OLS) regression model was employed for analysis. The results demonstrate a statistically significant negative impact of fiscal deficits on capital expenditure allocations, indicating that deficit financing crowds out public investment. Conversely, both IGR and federal allocations exhibited positive and significant effects, though the latter underscores a dependency on external funds. The study concludes that entrenched fiscal indiscipline, characterized by persistent deficits, is a primary constraint on Kogi State’s ability to fund human development initiatives transparently and accountably. We recommend the stringent enforcement of fiscal responsibility legislation, a deliberate strategy for IGR diversification beyond the oil sector, and the institutionalization of robust public access to information protocols to ensure the accountable use of all public funds.